PREVALENCE OF SOCIO-EMOTIONAL PROBLEMS IN SCHOOL-AGED ADOLESCENTS OF ARMY PUBLIC SCHOOLS OF RAWALPINDI - Zafar, Dr. Shazeena; Johar, Dr. Nigar; Haseeb, Dr. Farhana; Azam, Dr. Naila; Mahmood, Dr. Humaira; Pervaiz, Dr. Farrah (Pakistan Armed Forces Medical Journal, 2019)
Introduction: Socio-emotional problems in adolescents cause considerable morbidity and social incapacity, but knowledge regarding its actual prevalence in Army public schools is limited. Objective: To assess the prevalence of socio-emotional problems in school-aged adolescents of Army Public schools of Rawalpindi. Study Design: Descriptive cross sectional study. Place and Duration of Study: Study was conducted in the Army Public School and College Fort Road Rawalpindi, from Mar to Sep 2018. Materials and Methods: Class 8th students (males and females) of Army Public school Fort Road were recruited through universal sampling. Strength and Difficulty Questionnaire was administered to assess the socioemotional status of adolescents and relationship with age and gender was assessed. Results: Of the 320 students, 292 (91%) questionnaires were completed. On the basis of standard cut offs 54% of the students were in normal category, 19% were borderline at risk, 17% in high risk and 10% in very high risk category. Gender wise analysis of the individual behavioral scores showed significant results for emotional problems (p-value=0.029), hyperactivity (p-value=0.001), prosocial behavior (p-value=0.006) and total difficulty scores (p-value=0.048). For age (below and above mean), significant results were observed for hyperactivity (p-value=0.04), prosocial behavior (p-value=0.043) and total difficulty scores (p-value=0.018). Conclusion: Study being a part of the feasibility trial of School mental health project in APSACS will help to provide an insight into the burden of the issue in order to formulate integrated promotional and preventive services.